Estimating annual rate of decline: prospective, longitudinal data on arm tremor severity in two groups of essential tremor cases. Issue 7 (24th March 2011) - Louis, Elan D; Agnew, Angus; Gillman, Arthur; Gerbin, Marina; Viner, Amanda S
Abstract : Background: Despite its high prevalence, there are surprisingly few prospective, longitudinal data on the clinical course of essential tremor (ET). Patients themselves often want to know from their treating physician whether and by how much their tremor is expected to worsen over time. Methods: As part of two research protocols, prospective, longitudinal data were collected on tremor severity in two samples of ET cases (44+39 cases, combined n=83). At a baseline and one follow-up evaluation, a detailed clinical assessment was performed and action tremor in the arms was rated by a senior movement disorders neurologist using a standardised clinical rating scale (Total Tremor Score (TTS), range 0–36). Results: In the first case sample, TTS increased annually by 0.32±0.89 points (ie, an annual increase of 5.3±17.1% (median 1.8%) from the mean baseline score). TTS increased by ≥0.5 points in 23/24 (95.8%) cases followed for ≥5 years. In the second sample, TTS score increased annually by 0.64±1.49 points (annual increase of 3.1±8.1% (median 2.0%) from the mean baseline score). TTS increased by ≥0.5 points in 11/15 (73.3%) cases followed for ≥5 years. No baseline factors were identified that predicted annual change in TTS. Conclusions: Most ET cases exhibited a progressive worsening in tremor scores with time such that the average annual increase in tremor severity from baseline was estimated to be between 3.1% and 5.3% and the median annual increase from baseline was between 1.8% and 2.0%. These published estimates will hopefully be a useful prognostic guide for clinicians and their patients.